The microRNA FEW RHIZOIDS1 controls rhizoid patterning in the liverwort Marchantia polymorpha - Thamm, A (2019)
MicroRNAs (miRNAs) control gene expression and consequently play regulatory roles in the development of plants and animals. The FEW RHIZODS 1 (MpFRH1) miRNA of the liverwort Marchantia polymorpha was identified as a negative regulator of rhizoid development. ROOT HAIR DEFECTIVE 6-LIKE (RSL) class I basic Helix-Loop-Helix transcription factors (TFs) positively regulate rhizoid development in bryophytes and root hair development in angiosperms, thus being conserved positive regulators of tip-growing cells with a rooting function in land plants. Here, I demonstrate that MpFRH1 directly targets the MpRSL1 mRNA, the only RSL class I TF in M. polymorpha. While GLABRA2 (AtGL2) negatively regulates RSL class I TF expression in the angiosperm Arabidopsis thaliana, the function of MpFRH1 as a negative regulator of RSL class I TFs in liverworts demonstrates that independent mechanisms evolved to repress RSL class I TF expression in different land plant lineages. To determine how MpFRH1 represses rhizoid development I generated loss of function (LOF) mutations in the MpFRH1 gene. I showed that rhizoid initials develop larger clusters in Mpfrh1LOF plants than in wildtype. Furthermore, the lack of MpFRH1 activity causes the development of supernumerary mucilage papillae cells and meristematic notches. These findings indicate that MpFRH1 suppresses the development of ectopic epidermal structures such as rhizoid cells and mucilage papillae cells as well as apical cells in meristems. By combining functional and spatiotemporal expression data of both MpFRH1 and MpRSL1, using promoter reporter constructs, an MpFRH1 activity biosensor and in situ hybridizations, I suggest that MpFRH1 may act as a mobile miRNA required for lateral inhibition during epidermal patterning formation.